Partisan intergovernmental transfers: empirical evidence, political and economic effects, and the electoral rationale - Bugarin, Maurício S.; Ferreira, Ivan (Revista do Serviço Público, 2021)
This article discusses the stylized fact of politically motivated intergovernmental transfers, according to which a higher level of public administration (federal or state government) transfers greater resources to lower levels (states or municipalities) when the same party holds the Executive in both levels. First, it shows that it is a pervasive phenomenon in the world in general and in Brazil in particular. Then, it discusses its effects on subnational electoral equilibria and on the performance of the public administration. Finally, it builds a political economy model that explains the electoral rationale behind this stylized fact.